Analysis of Entropy trajectories in very Heavy Fermions for Adiabatic Demagnetization Refrigeration at the T<1K range - Sereni, Julian Gustavo Renzo (Elsevier, 2019)
Fil: Sereni, Julian Gustavo Renzo. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina